Uterine rupture at 28 weeks of gestation after laparoscopic myomectomy – a case report - Tomczyk, Katarzyna M.; Wilczak, Maciej; Rzymski, Paweł (Menopause Review/Przegląd Menopauzalny, 2018)
There are many reasons for sterility, and uterine malformations are of the greatest concern. Among uterine disorders, myomas play a significant role and are present in 27% of infertile women. The occurrence of myomas is frequent – 20-40% in women of reproductive age. Thus, for those infertile patients surgical treatment may be needed to preserve an opportunity to conceive. This case report refers to an uterine rupture at 28 weeks of gestation after laparoscopic myomectomy (3 months before conceiving). The myomectomy was conducted correctly and two layers of sutures on the myometrium were performed. The purpose of the myomectomy in a young woman should be well considered. In cases of infertility, removal of the lesions is usually necessary to give the patient a chance of pregnancy. At the same time, the risk of uterine rupture is increased. There are some suggestions referring to myomectomy to reduce the risk of uterine rupture in a subsequent pregnancy. It seems that the method of sewing the uterine closure is crucial. For example, multilayer uterine stitches, preservation of the endometrial cavity, and avoidance of using electrosurgery to prevent devascularization (to avoid haematoma formation) should be taken into consideration to prevent weakness of the wall of the uterus. Uterine scars differ histologically and biochemically.